2008
DOI: 10.1007/s12032-008-9106-7
|View full text |Cite
|
Sign up to set email alerts
|

Palliative chemotherapy for non-transitional cell carcinomas of the urothelial tract

Abstract: Non-transitional cell carcinomas of the urothelial tract comprise 5-10% of urothelial cancers. Clinical information regarding the clinical behavior and chemotherapy outcome of non-transitional cell carcinomas of the urothelial tract are incomplete due to their rarity. The object of this study was to evaluate the clinical features and the efficacy of palliative chemotherapy in advanced non-transitional cell carcinomas of the urothelial tract. We analyzed the clinical records of 21 consecutive patients who recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 18 publications
3
30
0
Order By: Relevance
“…Our multivariate analysis showed that factors affecting OS were advanced age, stage IV disease, and poor ECOG performance status. In our study, the median survival times of patients with SqCC and those with AC receiving platinum-based treatment during the metastatic period were 7.7 and 30.3 months, respectively, in accordance with the literature [27]. The ORR was 33% for AC and SqCC, and the stable disease rates were 33% and 0.0% for AC and SqCC, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Our multivariate analysis showed that factors affecting OS were advanced age, stage IV disease, and poor ECOG performance status. In our study, the median survival times of patients with SqCC and those with AC receiving platinum-based treatment during the metastatic period were 7.7 and 30.3 months, respectively, in accordance with the literature [27]. The ORR was 33% for AC and SqCC, and the stable disease rates were 33% and 0.0% for AC and SqCC, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…However, differences in prognosis are not as apparent when adjusted for disease stage. In addition, it has been shown that nonpure urothelial histological variants demonstrate a different response to systemic therapies in a palliative setting compared with those with pure urothelial histology . Nevertheless, this cannot be translated into generalized recommendations regarding perioperative chemotherapy for patients with localized muscle‐invasive bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Although urothelial carcinoma with squamous differentiation may be associated with poor prognosis, conflicting data have been reported regarding the role of squamous differentiation in unfavorable clinical outcomes. 7,[10][11][12][13][14][15][16] Because it is not uncommon for squamous differentiation to concurrently occur with other histological variants of urothelial carcinoma, such as micropapillary, glandular, and sarcomatoid differentiation, studies that report on mixed urothelial carcinoma variants may contribute to the discrepancies. 10,17,18 In this study, our aim was to compare tumor pathological stage and status of pelvic lymph-node metastasis between invasive urothelial carcinoma and urothelial carcinoma with squamous differentiation in patients who underwent cystectomy.…”
Section: Introductionmentioning
confidence: 99%